Implementation and data mining of external biological databases - Langraf, V.; Petrovičová, K.; Brygadyrenko, V. V. (Regulatory Mechanisms in Biosystems, 2025)
The implementation of external biological databases is a key approach that allows researchers to consolidate scattered information from different sources into a collaborative unified system. In practice, this means that data from projects such as GenBank, UniProt, and Ensembl are automatically retrieved, transformed into a unified format, and stored in a relational or NoSQL database using ETL processes. This approach ensures that sequence data, gene ann o tations, or protein information are always consistent and ready for further analysis, eliminating the risk of manual copying or incorrect mapping of entities. The aim of this study was to design and implement a process for integrating data from an external ITIS (Integrated Taxonomic Information System) into a relational database in a Microsoft SQL Server environment. After analysing the ITIS schemas and data formats, we prepared tools for automated ETL (E x tract, Transform, Load), which loaded 19 source files with taxonomic and metadata data using bulk import (BULK INSERT). Data normalisation and consistency checking ensured reliable linking of entities (identifiers, authors, comments, and vernaculars). To demonstrate the usefulness of the solution, we performed a preliminary SQL data extraction analysis: we found that the database contains 107,540 unique references to genera , of which the most numerous is the genus Euphorbia (5,009 records); the most comments on taxa were added in 2015 and 2001; and the highest frequency of publications was recorded in 2018 -2023 . These results confirm the suitability of MS SQL for systematic taxonomy studies and open up space for further automation of updates and expansion of the analysis to include temporal or geolocation trends.